Análise da produtividade dos insumos usados na cultura do milho região de Viçosa, Zona da Mata, Minas Gerais, em 1868/1869 - Borzino Ferreira da Silva, Sérgio Luiz; Leitão e Silva, Josué; Dias Teixeira, Teotônio (Revista Ceres, 2025)
The present study made in the region of Viçosa, in the «Zona da Mata» of Minas Gerais, had as its objective to investigate the profitability of the inputs employed in corn production. Through the use of a production function, the marginal productivities of the resources were estimated. Their prices, together with the product prices, suggested the optimum combinations of these resource. The presently employed technology was compared with the recommended technology in order to test which of the two is more profitable and to learn the requirements for introducing the new technology.